2021
DOI: 10.15537/smj.2021.42.7.20210110
|View full text |Cite
|
Sign up to set email alerts
|

Association between sex hormones and migraine in young Saudi females

Abstract: Objectives: To assess the sex hormone levels in young Saudi female migraineurs during a migraine attack and during pain-free periods and compare them with control subjects. Methods:A case-control study involving 14 Saudi female migraineurs and 21 control subjects was conducted between December 2019 and March 2020. Demographic and disease history data were collected through participant interviews. Blood samples were drawn during the migraine attack and pain-free periods.Results: Follicular (30.00±19.60; p<0.001… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…One study (Shields et al, 2019) was included though it displayed high risk as it compared migraineurs to laboratory norms rather than healthy controls (Shields et al, 2019); inclusion was justified based on the consideration of laboratory norms to be equivalent to a healthy control population. Another study was excluded based on the risk of bias (Al Asoom et al, 2021) due to insufficient power, ictal measurement of estrogen and progesterone (whereas all other estrogen/progesterone studies measured interictally [Nagel‐Leiby et al, 1990; de Lourdes Figuerola et al, 1997; Kibler et al, 2005; Yucel et al, 2005; Ibrahimi et al, 2015; Li et al, 2018]), and significantly different body mass index between control and non‐menstrually related migraine groups. As body mass index has previously been reported to be positively correlated with estrogen levels, this potentially confounded results (Siiteri, 1987).…”
Section: Resultsmentioning
confidence: 99%
“…One study (Shields et al, 2019) was included though it displayed high risk as it compared migraineurs to laboratory norms rather than healthy controls (Shields et al, 2019); inclusion was justified based on the consideration of laboratory norms to be equivalent to a healthy control population. Another study was excluded based on the risk of bias (Al Asoom et al, 2021) due to insufficient power, ictal measurement of estrogen and progesterone (whereas all other estrogen/progesterone studies measured interictally [Nagel‐Leiby et al, 1990; de Lourdes Figuerola et al, 1997; Kibler et al, 2005; Yucel et al, 2005; Ibrahimi et al, 2015; Li et al, 2018]), and significantly different body mass index between control and non‐menstrually related migraine groups. As body mass index has previously been reported to be positively correlated with estrogen levels, this potentially confounded results (Siiteri, 1987).…”
Section: Resultsmentioning
confidence: 99%
“…Globally, the proportion of adults with headaches is 65 %; 42 % for tension-type headache, 20 % for migraine, and 3 % for chronic headaches [11] . In Saudi Arabia, the incidence of migraine, in general, is 26.97 %, with women having three times the frequency of men [12] .…”
Section: Introductionmentioning
confidence: 99%
“…One study indicated prevalence of migraine among women is 18.2 %, and only 6.5 % among men. Some hypothesized the role of sex hormones (mainly Oestrogen) in the pathophysiology of migraine which could explain its higher prevalence among females [12] .…”
Section: Introductionmentioning
confidence: 99%
“…Hemiplegic migraine is another type of MA and is a severe and rare condition that affects one side of the body and causes temporary numbness [ 9 ]. It once was believed that migraine is a vascular disease; however, many recent types of research confirmed the involvement of multiple mechanisms related to the brain structures and processes [ 10 ]. Furthermore, accumulated evidence demonstrates a genetic background for the transmission of the disease.…”
Section: Introductionmentioning
confidence: 99%